Finitely Represented K-Marked Quivers - Belousov, K. I.; Nazarova, L. A.; Roiter, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We present necessary and sufficient conditions for the finite representability of K-marked quivers.